2007
DOI: 10.1155/2007/906417
|View full text |Cite
|
Sign up to set email alerts
|

Parietal Dysgraphia: Characterization of Abnormal Writing Stroke Sequences, Character Formation and Character Recall

Abstract: Objective: To characterize various dysgraphic symptoms in parietal agraphia. Method: We examined the writing impairments of four dysgraphia patients from parietal lobe lesions using a special writing test with 100 character kanji (Japanese morphograms) and their kana (Japanese phonetic writing) transcriptions, and related the test performance to a lesion site. Results: Patients 1 and 2 had postcentral gyrus lesions and showed character distortion and tactile agnosia, with patient 1 also having limb apraxia. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 38 publications
4
47
0
Order By: Relevance
“…They observed that while Kana writing-to-dictation and copying Kanji were preserved in these AD patients, writing to dictated Kanji words was impaired. The impaired writing of dictated Kanji words was associated with dysfunctional cortical activity predominantly in the left frontal, parietal and temporal brain regions [43] consistent with other Japanese dysgraphia studies [44][45][46]. The present observations of dysgraphia associated with deficits in semantic memory that were exacerbated acutely by the writing task appear to fit current notions pertaining to the progressive performance impairments of AD patients within language and cognition domains from a staging perspective [47,48].…”
Section: Discussionsupporting
confidence: 88%
“…They observed that while Kana writing-to-dictation and copying Kanji were preserved in these AD patients, writing to dictated Kanji words was impaired. The impaired writing of dictated Kanji words was associated with dysfunctional cortical activity predominantly in the left frontal, parietal and temporal brain regions [43] consistent with other Japanese dysgraphia studies [44][45][46]. The present observations of dysgraphia associated with deficits in semantic memory that were exacerbated acutely by the writing task appear to fit current notions pertaining to the progressive performance impairments of AD patients within language and cognition domains from a staging perspective [47,48].…”
Section: Discussionsupporting
confidence: 88%
“…They observed that while Kana writing-to-dictation and copying Kanji were preserved in these AD patients, writing to dictated Kanji words was impaired. The impaired writing of dictated Kanji words was associated with dysfunctional cortical activity predominantly in the left frontal, parietal and temporal brain regions [41] consistent with other Japanese dysgraphia studies [42][43][44]. The present observations of dysgraphia associated with deficits in semantic memory that were exacerbated acutely by the writing task appear to fit current notions pertaining to the progressive performance impairments of AD patients within language and cognition domains from a staging perspective [45,46].…”
Section: Discussionsupporting
confidence: 88%
“…Apraxic agraphia is defined as having the following deficits [12]: (1) illegible graphemes in writing that cannot be accounted for by sensorimotor dysfunction, (2) grapheme production improves with copying, (3) preserved oral spelling or typing, and (4) disordered writing stroke sequences [13]. Apraxic agraphia has also been reported following a lesion of the dorsomedian nucleus of the thalamus [3].…”
Section: Discussionmentioning
confidence: 99%
“…For example, we have reported patients with somesthetic dysgraphia in which deficits of combined sensations (texture recognition, two-point discrimination and graphesthesia) in the digits yielded poor character formation [12]. As the ventroposterolateral (VPL) nucleus of the thalamus receives ascending fibers from the , roll) b Deformity was evaluated only for correct responses.…”
Section: Discussionmentioning
confidence: 99%